2013
DOI: 10.1038/srep01731
|View full text |Cite
|
Sign up to set email alerts
|

The stratum corneum comprises three layers with distinct metal-ion barrier properties

Abstract: The stratum corneum (SC), the outermost barrier of mammalian bodies, consists of layers of cornified keratinocytes with intercellular spaces sealed with lipids. The insolubility of the SC has hampered in-depth analysis, and the SC has been considered a homogeneous barrier. Here, we applied time-of-flight secondary ion mass spectrometry to demonstrate that the SC consists of three layers with distinct properties. Arginine, a major component of filaggrin-derived natural moisturizing factors, was concentrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 50 publications
(71 reference statements)
3
52
0
Order By: Relevance
“…Kubo et al reported that the function of the SC is different in the upper, middle, and deeper regions. 20) They suggested that the structure of the upper part of the SC has some porosity, which is easily penetrated by low molecular weight compounds. C 0 ′ correlated with the concentration of the boundary face of the second phase, so it is important to clarify why the skin penetration of ufenamate in strips 1-6 of the SC was enhanced when ufenamate was applied with liquid vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Kubo et al reported that the function of the SC is different in the upper, middle, and deeper regions. 20) They suggested that the structure of the upper part of the SC has some porosity, which is easily penetrated by low molecular weight compounds. C 0 ′ correlated with the concentration of the boundary face of the second phase, so it is important to clarify why the skin penetration of ufenamate in strips 1-6 of the SC was enhanced when ufenamate was applied with liquid vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Filaggrin and its metabolites bind nickel, and it is possible that it also binds other metals and may also be of importance to the penetration and accumulation of amalgam and consequently infl uence the risk of allergy to amalgam. Along this line, the results of a recent study on mice (tails) suggest that the stratum corneum barrier can be weakened against penetration of particular small metal ions, e.g., Cr (chromium) (III), by fi laggrin defi ciency [ 26 ].…”
Section: A Role For Filaggrin In Oral Contact Allergic Lesions?mentioning
confidence: 97%
“…Lipid-rich matrix is used for the transdermal delivery (TDD)-intercellular pathway, and it is composed of hydrophilic domain-head of ceramides and lipophilic domain-tail of cermaides. The stratum corneum can be divided into three main layers with different compositions and barrier functions [30]. The layers can be characterized by the concentration of K, Na, ceramides and fillagrin (Figure 3).…”
Section: Stratum Corneum Structurementioning
confidence: 99%